2022
DOI: 10.3390/ijms232214420
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Modulation of Human Stem Cells from the Apical Papilla by Species Associated with Dental Root Canal Infection

Abstract: Interaction of oral bacteria with stem cells from the apical papilla (SCAP) can negatively affect the success of regenerative endodontic treatment (RET). Through RNA-seq transcriptomic analysis, we studied the effect of the oral bacteria Fusobacterium nucleatum and Enterococcus faecalis, as well as their supernatants enriched by bacterial metabolites, on the osteo- and dentinogenic potential of SCAPs in vitro. We performed bulk RNA-seq, on the basis of which differential expression analysis (DEG) and gene onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…Although the treatment protocol we used is standardized and we applied passive ultrasonic irrigation [ 50 ], these efforts might not be enough to eliminate the bacterial biofilm. Furthermore, low concentrations of irrigation solutions have been proposed due to concerns about the potential cytotoxicity of high concentrations of NaOCl solutions on stem cells of the apical papilla [ 51 ]: the higher concentrations of NaOCl used, the more cytotoxic effects on survival and differentiation of the stem cells [ 52 , 53 ]. In fact, it has been found that even if bacterial levels are reduced when using 6% NaOCl concentration, a total elimination of the microorganisms might not be guaranteed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the treatment protocol we used is standardized and we applied passive ultrasonic irrigation [ 50 ], these efforts might not be enough to eliminate the bacterial biofilm. Furthermore, low concentrations of irrigation solutions have been proposed due to concerns about the potential cytotoxicity of high concentrations of NaOCl solutions on stem cells of the apical papilla [ 51 ]: the higher concentrations of NaOCl used, the more cytotoxic effects on survival and differentiation of the stem cells [ 52 , 53 ]. In fact, it has been found that even if bacterial levels are reduced when using 6% NaOCl concentration, a total elimination of the microorganisms might not be guaranteed [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, microbial correlations with host phenotype might jeopardize the treatment outcomes of PR [ 76 ]. In the presence of bacterial species, the immune and inflammatory response of SCAPs is upregulated, but cell division and proliferation are downregulated [ 51 ]. Data obtained from animal models confirm that bacteria present even as a low-grade infection have negative effects on bone healing [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our past studies, we have shown how short-term modulation of SCAP by bacteria can affect their viability, immune response, and gene expression for osteogenesis and dentinogenesis ( Razghonova et al., 2022 ; Zymovets et al., 2022 ). However, to assess whether bacterial influence alone, without the presence of osteo/dentinogenic induction medium, can stimulate SCAPs mineralization and thus influence their differentiation potential, a minimum of 21 days of bacterial exposure is required, which is the necessary duration for cell differentiation ( Abuarqoub et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The BDNF, GM-CSF, and VEGF-A, were chosen for their important role in osteo/odontogenic cells differentiation and regeneration ( Saito et al., 2011 ; Kolar et al., 2017 ; Liu et al., 2018 )). The pro-inflammatory markers—IL-8, IL-6, MCP-1, and IL-17A were selected based on the results of previous studies, indicating the upregulation of these markers in SCAPs under bacterial influence ( Razghonova et al., 2022 ; Zymovets et al., 2022 ) as well as IL-1a and IL-1β, as they are involved in innate pro-inflammatory response ( Dinarello, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation